Cannabis: A Cognitive Illusion (2017)
Introduction The vision of cannabis as a soft drug is due to the low risk perception that young and old people have of the drug. This perception is based on erroneous beliefs that people have about the drug. Objective To compare the beliefs of cannabis use and consequences among adolescents with a lifetime prevalence of cannabis use and those without a lifetime prevalence of cannabis use. Method Quantitative, descriptive and cross-sectional study with a probability sample of 156 high school students who completed an ad-hoc questionnaire that included sociodemographic data and 22 questions about the beliefs that young people had about cannabis use and its consequences. Results The lifetime prevalence of cannabis use was 13.5%. The prevalence group consisted mostly of males. Statistically significant differences between different groups and different beliefs were found. The group with no lifetime prevalence of cannabis use perceived higher risk as regards the damage that cannabis can cause to memory, other cognitive functions, neurons, mental health, and general health. The group with a lifetime prevalence of cannabis use perceived a lower risk as regards the use of cannabis, and think that intelligent people smoke cannabis, and that cannabis has positive effects on the brain, increasing creativity. and is used to cure mental diseases. Conclusions Those who used cannabis once in their life perceive the use of the substance as less harmful or less potential danger to health compared to those who never consumed. In fact those who consumed at some time even have beliefs that suggest positive effects in those people that consume it. © 2016 Asociación Colombiana de Psiquiatría